2009
DOI: 10.1242/dev.032235
|View full text |Cite
|
Sign up to set email alerts
|

The tetraspanin Tm4sf3 is localized to the ventral pancreas and regulates fusion of the dorsal and ventral pancreatic buds

Abstract: During embryogenesis, the pancreas develops from separate dorsal and ventral buds, which fuse to form the mature pancreas. Little is known about the functional differences between these two buds or the relative contribution of cells derived from each region to the pancreas after fusion. To follow the fate of dorsal or ventral bud derived cells in the pancreas after fusion, we produced chimeric Elas-GFP transgenic/wild-type embryos in which either dorsal or ventral pancreatic bud cells expressed GFP. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…Tm4sf4 is involved in intestinal progenitor cell adhesion and migration during differentiation of intestinal crypt cells (Diosdado et al, 2004;Wice and Gordon, 1995). Recently in Xenopus, Tm4sf3 was described to regulate dorsal and ventral pancreatic bud fusion and ventral bud cell migration, and independently appeared to inhibit ventral b cell differentiation (Jarikji et al, 2009). We believe Tm4sf4 plays a role during endocrine pancreas specification, promoting progenitor cell adhesion to the ductal epithelium and inhibiting migration of the differentiating Ngn3 + population.…”
Section: Ngn3mentioning
confidence: 99%
“…Tm4sf4 is involved in intestinal progenitor cell adhesion and migration during differentiation of intestinal crypt cells (Diosdado et al, 2004;Wice and Gordon, 1995). Recently in Xenopus, Tm4sf3 was described to regulate dorsal and ventral pancreatic bud fusion and ventral bud cell migration, and independently appeared to inhibit ventral b cell differentiation (Jarikji et al, 2009). We believe Tm4sf4 plays a role during endocrine pancreas specification, promoting progenitor cell adhesion to the ductal epithelium and inhibiting migration of the differentiating Ngn3 + population.…”
Section: Ngn3mentioning
confidence: 99%
“…For example, by producing chimeric embryos where either the dorsal or ventral pancreatic bud was labeled we demonstrated that the ventral pancreatic bud cells migrate extensively into the dorsal bud after fusion while dorsal pancreatic bud cells do not (Fig. 1b) [11••]. By isolating individual dorsal and ventral pancreatic buds we compared their gene expression profiles and identified several new genes involved in regulating cell fate specification and proliferation in the developing pancreas [11, 36, 37].…”
Section: Pancreas Developmentmentioning
confidence: 99%
“…By isolating individual dorsal and ventral pancreatic buds we compared their gene expression profiles and identified several new genes involved in regulating cell fate specification and proliferation in the developing pancreas [11, 36, 37]. We showed that the tetraspanin, tm4sf3 , was localized to the ventral pancreas and regulates fusion of the dorsal and ventral buds [11], whereas the RNA binding protein Celf3 controls proliferation in the developing endoderm through translational activation of key cell cycle genes. By producing different fusion proteins between Celf3 and Celf1 we identified the linker region of Celf3 as responsible for the translational enhancement activity on cyclin A2 mRNA [36].…”
Section: Pancreas Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetraspanins are a family of evolutionarily highly conserved proteins which influence a wide variety of physiologic processes and diseases, among others protein trafficking [Berditchevski and Odintsova, 2007], modulation of immune-signaling complexes [Levy and Shoham, 2005], and cancer [Z€ oller, 2009]. The regulated expression of TSPAN8 (also known as TM4SF3 or CO-029) is important for early development of the pancreas [Jarikji et al, 2009] and TSPAN8 protein abundance is known to be positively correlated with tumor progression , similar to tetraspanins CD151 (TSPAN24) [Yang et al, 2008] or TSPAN1 [Scholz et al, 2009] and opposite to, for example, CD9 (TSPAN29) [De Bruyne et al, 2008] or CD82 (TSPAN27) [Miranti, 2009], whose protein expression is negatively correlated with malignant phenotype. Besides the severe impact of expression changes of TSPAN8 and tetraspanins in general, mutations in TSPAN7 (CD231, TM4SF2) resulting in the amino acid substitution P172H lead to X-linked mental retardation [Zemni et al, 2000;Maranduba et al, 2004].…”
Section: à6mentioning
confidence: 99%